Disposition: An Approachable Ontology - Prelock, Aaron R (New blackfriars, 2022)
Reformed Scholastic John Owen's appropriation and adaptation of Thomas Aquinas’ development of the classical ‘disposition’ (Latin: habitus) concept offers practical insight into seventeenth century faculty psychology. This article argues that Owen not only borrows deliberately from Aquinas, he also attempts to simplify and even improve upon Aquinas’ more complicated theological, philosophical, and psychological insights in this important area. While he deals with dispositions of the mind, will, and affections in a way that is broadly similar to Aquinas’ ontological understanding, Owen's most significant contribution to seventeenth century faculty psychology and its theological use is a sustained and consistent emphasis on the necessity of virtuous affections in the pursuit of communion with God. Examining this concept also provides greater context for how the Reformed Scholastics were able to interact with their medieval counterparts. In this we see the Reformed Scholastics’ continuity with the Christian tradition and their depth of understanding regarding human nature.